Quality seeds in Nigeria: IPSR Innovation Profile - Morris, S.; van den Berg, Marco (CGIAR System Organization, 2024)
Two main innovations are improved seed varieties and the extension approach of the East West Seeds - Knowledge Transfer (EWS-KT) . The improved vegetable seed varieties result from advanced breeding techniques by East-West Seed with enhanced traits like yield, disease resistance, and adaptability to diverse conditions. Improved vegetable seed varieties empower smallholder farmers’ production capacity, increasing productivity while conserving resources. This ensures that agriculture remains at the forefront of sustainable development and food security. The extension approach provides timely, accessible, and tailored information to smallholder farmers via EWS-KT’s extension agents, enhancing their decision-making and crop management. It also encompasses the innovative approaches of publicly certifying trained farmers – to increase innovation diffusion and product value – and educating smallholder farming households to optimize income use through an inclusive decision-making process. These innovative approaches hope to empower farmers with actionable knowledge for sustainable farming that can better their livelihoods.